Sustainable Ecosystem: Edukasi Teknik Ecoprint Zat Warna Alam Mahoni bagi Masyarakat Kelurahan Kalisegoro, Kota Semarang: indonesia - Widowati, Widowati; Atika, Atika; Sholikhah, Roudlotus Sholikhah; Nurmasitah, Sita; Asih, Dwi Putri (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
In 2023, UNNES won the Most Sustainable University award at the UI Greenmetric World University ranking event. This is the 5th national ranking out of a total of 145 universities and the 37th world ranking out of a total of 1,183 universities in the world. This achievement is proof of UNNES' consistency as a conservation-oriented university. In line with this commitment, each lecturer in the study program develops various research related to work based on sustainability. One of the things that is being created is using natural dyes in textile products. Natural dyes from Mahogany bark (Swietenia mahagoni) have the potential to be a source of natural dyes. Data from the UNNES Conservation Development Agency notes that there are 12,320 Mahogany trees around the UNNES campus. This means that the availability of Mahogany trees is very large if used as a natural dye. With this potential, a problem identification was carried out, then it was found that many housewives needed skills to support family income. This was found in the Kalisegoro Village community group. Thus, training and education will be carried out by providing skills in the form of ecoprint training for the PKK mothers' group in Kalisegoro Village. It is hoped that women can become the pillars of poverty alleviation, especially for their families. The output targets in this program are national journal publications, information to print or online media, and video profiles of activity implementation.